Veterans Affairs Training Experiences During the COVID-19 Pandemic-Trainee Satisfaction and Interest in Future Veterans Affairs Employment: A National Survey - Anne R. Griffin MPH, BSN, RN; Jia Bai MPH; Heather Northcraft MA; Aram Dobalian PhD, JD, MPH (SAGE Publishing, 2024)
Introduction The emergence of COVID-19 caused a sudden, unexpected disruption in the clinical training experiences of nurse trainees at the US Department of Veterans Affairs (VA), the largest clinical training setting in the US for nurses. Purpose To understand associations between COVID-19 and nurse trainees' satisfaction with their training experiences and the likelihood that they would consider future VA employment. Methods A cross-sectional design was used to assess 7,890 nurse responses from the VA's Trainee Satisfaction Survey for academic years 2018-2021. Results After the pandemic, trainees reported decreased training satisfaction (95.06% vs. 93.46%; P  = .0028). Willingness to consider future VA employment was unchanged. Patient case mix, the onboarding process, and challenges with other staff were the most common reasons for dissatisfaction. Conclusion Nurse trainees expressed a small but statistically significant degree of dissatisfaction with their clinical learning environment during this study period but their willingness to seek employment with the VA remained high.